Dietary assessment in intermittent fasting: validation of a short food frequency questionnaire vs. food records in diurnal dry fasting and time-restricted eating - Schüssler, Isabelle C.; Pappe, Christina L.; von Scheidt, Christel; Peters, Beeke; Dommisch, Henrik; Kessler, Christian; Michalsen, Andreas; Koppold, Daniela A.; Pivovarova-Ramich, Olga (Frontiers in Nutrition, 2025)
ObjectivesFood frequency questionnaire (FFQ) is a cost-effective method of dietary assessment in nutritional and clinical research. It can be easily adapted to different research questions or populations, but modified versions require careful validation. This study assessed the validity of a short 14-item semi-quantitative FFQ compared to weighted food records in a secondary analysis of an intermittent fasting trial.MethodsDietary assessment was conducted during the ParoFastin study, a controlled trial investigating the effects of religious Bahá’í fasting (19 days of diurnal dry fasting) and 16:8 time-restricted eating (TRE) on oral health and metabolic state compared to the habitual food intake. Daily consumption of meals, snacks, food groups, and overnight fasting time were assessed using both the short FFQ and food records. Food records were collected for 1 week at baseline and 19–21 days during the intervention and analyzed using PRODI®, a professional dietary assessment software. The FFQ was completed once at baseline and twice during the intervention. Its validity was assessed using correlation and method agreement analysis, including Bland–Altman plots for continuous data. Energy and macronutrient intakes were quantified using food records only.ResultsEight men and seven women, with a median age of 29 (27–34) years, were included in the validation analysis. Correlation coefficients ranged from 0.189 (tendency to snack) to 0.893 (meat consumption). Tendency to snack, frequency of snack consumption, and frequency of whole grain consumption showed insufficient agreement between the two methods. However, most questions of the short FFQ were found to be statistically valid in this population. According to food records, the energy, fat and carbohydrate intake were reduced during the Bahá’í fast and remained unchanged in the control and TRE groups compared to the baseline, while analysis of these parameters was not feasible based on the short FFQ.ConclusionOverall, good agreement for the methods was found, although data on snack tendency, frequency of snack consumption, and whole-grain consumption were unreliable, indicating a need for questionnaire modifications. In contrast to time-consuming food records, the short FFQ can be effectively used in clinical trials and medical practice for specific goals.Clinical trial registrationhttps://drks.de/search/de/trial/DRKS00026701 German Clinical Trials Register (DRKS); identifier DRKS00026701.